Thermoelastic fracture analysis of functionally graded materials using the scaled boundary finite element method. (1st April 2022) - Iqbal, M.D.; Birk, C.; Ooi, E.T.; Pramod, A.L.N.; Natarajan, S.; Gravenkamp, H.; Song, C.
Abstract: The scaled boundary finite element method is extended to model fracture in functionally graded materials (FGM) under coupled thermo-mechanical loads. The governing equations of coupled thermo-mechanical equilibrium are discretized using scaled boundary shape functions enriched with the thermal load terms. The material gradient is modeled as a series of power functions, and the stiffness matrix is calculated semi-analytically. Stress intensity factors and T − stress are directly calculated from their definition without any need for additional post-processing techniques. Arbitrary-sided polygon elements are employed for flexible mesh generation. Several numerical examples for isotropic and orthotropic FGMs are presented to validate the proposed technique. Highlights: SBFEM is developed for thermoelastic fracture in functionally graded materials. Polygon shape functions enriched for accurate representation of thermal stress. Stiffness matrices including material gradient are obtained semi-analytically. Singular stress fields and T − stress are accurately captured without post-processing.